Leadless pacemakers: does location matter?. (24th May 2021) - Menexi, C; Elrefai, M; Abouelasaad, M; Roberts, P
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction Leadless pacemakers (LPs) provide a viable alternative for patients who have an indication for pacing where transvenous pacing is not desirable or possible. Registries have demonstrated stable performance associated with LPs. There is preference towards implanting LPs into the trabeculated septum rather than the apex or free wall. We report our experience with the impact of the implantation site on acute and long-term electrical performance of LPs. Methods We ran a retrospective analysis on the first 100 LPS implanted at our centre. Two independent observers reviewed the fluoroscopic images and post-implant chest x-rays to classify the LPs' positions. We obtained the recorded pacing threshold, R-wave amplitude and impedance of the devices at the time of implant and at the latest available routine device follow-up. We used one-way ANOVA testing to compare the acute and long-term electrical performance of the LPs between different implantation sites. Results We were able to classify the site of the LPs implants in a total of 90 patient. 84 Patients (60% male) 57.3± 22.16 years were included .23.8% of the patients presented with syncope. Indications for pacing were symptomatic sinus node dysfunction (33.3%), high grade AV block (34.5%), bradyarrhythmia associated with atrial tachyarrhythmias (28.6%) and other indications (3.6%). We had a 100% successful implant rate, 85.7% required ≤2 attempts and 71.4% required one attempt. A total of 32 implants were in the apex (38.1%), 26 in mid-septum (30.9 %), 13 in the apical septum (15.5%), 12 on the septal aspect of the right ventricular inflow (14.3%) and 1 implant (1.2%) in the septum of the RV outflow tract. The follow up period of the 84 patients was 3.09 ± 1.97 years. 100% of the LPs had the pacing thresholds <2.0 V @0.24 ms at the time of implant. Pacing threshold, R-wave amplitude, and impedance averaged at 0.67 ± 0.41 V, 10.86 ± 5.41 mV, and 775 ± 193.28 Ohms respectively at the time of implantation and 0.66 ± 0.39 V, 14.08 ± 6.14 mV, and 564.29 ± 96.76 Ohms at the last device check. There was no statistically significant difference in either the pacing thresholds or the impedance between implant sites. Post hocTukey's analysis (excluding the outflow tract case) demonstrated significant statistical difference in the R-wave amplitudes between implants at the apex and the mid-septum both at the time of implantation (12.9 ± 6.1 mV and 8.53 ± 2.84 mV; p = 0.0196) and at follow up (15.97 ± 5.35 mV and 11.52 ± 5.01 mV; p = 0.0415). There were no differences between other sites Conclusions Our analysis demonstrated that aside from the difference between the sensed R wave amplitudes between LPs implanted at the apex and those implanted at mid-septum, there was no statistically significant difference in the acute or the long term electrical performance of implanted LPs regardless of the implantation site. A limitation to our analysis is the relatively low number of LP implants included in our analysis.